2023
DOI: 10.1186/s40561-023-00225-1
|View full text |Cite|
|
Sign up to set email alerts
|

UAE university students’ experiences of virtual classroom learning during Covid 19

Abstract: Virtual Classroom (VC) learning approaches have recently drawn considerable attention because they have the potential to encourage student engagement to ensure active and collaborative learning. Although research on online learning has gained visibility in recent times, VC learning has not received notable attention, especially in Gulf countries like the United Arab Emirates (UAE). The study examines students’ perception and experience of VC in a university in UAE during the COVID-19 pandemic in terms of its n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
(74 reference statements)
1
5
0
1
Order By: Relevance
“…It is interesting to read that 55% of the respondents agreed that course content is not well designed for distance education. This confirms what [20] concluded in their study that instructors and designers of virtual classroom courses need to lead and design modules to maximize the use of the virtual classroom and minimize any disadvantages such as a lack of face-to-face communication. Students also noticed that there are weaknesses in teaching methods and difficulties in communicating information remotely by instructors, which is in line with a major finding of [44] that applying innovative teaching methods minimizes the challenges that are faced in distance learning environments.…”
Section: Sub-domain 22 How Digital Infrastructure and Students' Readi...supporting
confidence: 83%
See 2 more Smart Citations
“…It is interesting to read that 55% of the respondents agreed that course content is not well designed for distance education. This confirms what [20] concluded in their study that instructors and designers of virtual classroom courses need to lead and design modules to maximize the use of the virtual classroom and minimize any disadvantages such as a lack of face-to-face communication. Students also noticed that there are weaknesses in teaching methods and difficulties in communicating information remotely by instructors, which is in line with a major finding of [44] that applying innovative teaching methods minimizes the challenges that are faced in distance learning environments.…”
Section: Sub-domain 22 How Digital Infrastructure and Students' Readi...supporting
confidence: 83%
“…As a consequence of the prolonged use of digital tools, psychological disorders and a drop in students' academic performance was observed in a study on students from Jordan universities [19]. Students at the UAE university [20] expressed their negative perception towards virtual classrooms that have proven effectiveness, but students may resort to this mode to continue addressing their learning needs. This is also the case at Saudi universities.…”
Section: Background 1perceptions Towards the Remote Mode Of Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Para Islam et al (2023), el aula virtual tiene el potencial de promover la participación del estudiante y garantizar un aprendizaje activo y colaborativo. La percepción y la experiencia de los estudiantes durante la Covid19 en una universidad de los Emiratos Árabes Unidos con 334 estudiantes ha permitido concluir que los estudiantes recurren al aula virtual no por su eficacia sino por sus necesidades de aprendizaje.…”
Section: Introductionunclassified
“…Following publication of the original article [ 1 ], the authors reported that the affiliations were missing in the submitted manuscript and were not present in the published article. The correct affiliations are presented in this correction article and the original article [ 1 ] has been updated.…”
mentioning
confidence: 99%